Integration of statistical process control (SPC) and engineering process control (EPC) in batch process - Sulaiman, Muhammad Haziq (2018)
Batch process is one of a main type of process in the chemical industry alongside continuous process. It is also called as discontinuous process due to the nature of the batch process. The main industry that utilizes batch process is the kind that produce low volume products and also, industry that produce specialty chemicals. The main principle of a batch process operations is by loading the reactants in a vessel and no material can be added or removed during the process. It is a very difficult encounter to production and process engineers to complete the task of achieving optimal performance of industrial batch processes. Batch processes have many major issues such as they are big batch-to-batch variations, highly non-linear dynamics, and difficulty in real-time measurement. It is significant to control the process in real-time, in order to avoid many issues such as off-spec product. The production of off-spec product is a major problem as the batch has to be eliminated and thus incurring loss. While the study of statistical process control (SPC) and engineering process control (EPC) is garnering attraction in controlling strategy, the implementing of the integration is still rare and few studies and research focus on it compare to continuous process. In this research, first, the real-time monitoring system of the integration of SPC and EPC in batch process is simulated. Secondly, the effectiveness of real- time monitoring systems of the integration of statistical process control and engineering process control in batch process is studied. The research revolves around a simulated case study of penicillin production. The type of control strategy deploy is the integration between SPC and EPC.